PENGARUH DIGITAL LITERACY TERHADAP KESIAPAN KERJA SISWA SMK MAITREYAWIRA BATAM - Valerian Yamin; Steffi Adam (Journal of Digital Ecosystem for Natural Sustainability, 2026)
This study aims to analyze the effect of digital literacy on student work readiness at SMK Maitreyawira Batam. The digital transformation occurring across various sectors of life, including education and the workplace, demands that individuals possess adequate digital literacy skills to compete and adapt to technological developments. Work readiness is a crucial factor for vocational high school graduates who are prepared to directly enter the industrial world. This research employs a quantitative approach using simple linear regression analysis. The population of this study consists of students at SMK Maitreyawira Batam, with sampling technique using probability sampling. Data collection was conducted through questionnaires measuring digital literacy levels, which include technological skills, understanding and evaluation of digital information, and attitudes toward technology, as well as work readiness encompassing the ability to work independently and in teams, work motivation, and mental readiness to face workplace pressures. The results indicate that digital literacy has a positive and significant effect on student work readiness. These findings suggest that the higher the level of digital literacy possessed by students, the higher their readiness to enter the workforce. This study provides implications for vocational education institutions to enhance digital literacy development programs in order to prepare competent graduates who are ready to face the challenges of an increasingly digitalized workplace.